Can Oxygen Utilization Rate Be Used to Track the Long‐Term Changes of Aerobic Respiration in the Mesopelagic Atlantic Ocean? - Guo, Haichao; Kriest, Iris; Oschlies, Andreas; Koeve, Wolfgang (Climate of the Past, 2023)
Quantifying changes in oceanic aerobic respiration is essential for understanding marine deoxygenation. Here we use an Earth system model to investigate if and to what extent oxygen utilization rate (OUR) can be used to track the temporal change of true respiration (Rtrue). Rtrue results from the degradation of particulate and dissolved organic matter in the model ocean, acting as ground truth to evaluate the accuracy of OUR. Results show that in thermocline and intermediate waters of the North Atlantic Subtropical Gyre (200–1,000 m), vertically integrated OUR and Rtrue both decrease by 0.2 molO2/m2/yr from 1850 to 2100 under global warming. However, in the mesopelagic Tropical South Atlantic, integrated OUR increases by 0.2 molO2/m2/yr, while the Rtrue integral decreases by 0.3 molO2/m2/yr. A possible reason for the diverging OUR and Rtrue is ocean mixing, which affects water mass composition and maps remote respiration changes to the study region.